Desain Kinematik Alat Pengumpan Material Berbasis Mekanisme Empat Batang - Syamsul Huda; Muhammad Jihad Islami; Mulyadi Bur (METAL: Jurnal Sistem Mekanik dan Termal, 2019)
In this paper was studied the design of feeding material system using four bars linkage mechanism. It was carried out dimensional synthesis of the mechanism based on the complex number method. This synthesis is applied to determine the length of crank, coupler, follower and dyad that control of feeding weight. Base on the results, it is obtained that the dimension of the four bars linkage and dyad to control 250 kg weight of feeding material  reprsented by lengths of crank, coupler and follower are 1 m, 2 m, and 1 m rspectively and two links of dyad 0.2 m and 0.75 m. It was also determined the constant of spring to support the opening of the feeding material, 23,18 kN/m  and input torque, 1083 Nm.